Simulation of Routing Probability in Ad Hoc Networks / Ahmad Zia Ul-Saufie Mohamad Japeri, Muhammad Hisyam Lee and Shaharuddin Salleh - Mohamad Japeri, Ahmad Zia Ul-Saufie; Lee, Muhammad Hisyam; Salleh, Shaharuddin (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2008)
An ad hoc network is a group of wireless mobile hosts forming a temporary network without the aid of any established infrastructure or centralized administration. In such an environment, it may be necessary for one mobile host to enlist the aid of other hosts in forwarding a packet to its destination due to the limited range of each mobile host's wireless transmissions. This paper presents the simulation and programming of a probability model for route selection of an ad hoc network for mobile computing. The route selection is based on the probability that the route is still available when a packet has to be sent through it. It is also based on the knowledge at each node of the geographic position of all the other nodes in the network and takes into account the mobility of the nodes and the dependencies between links in a computed route. We derive a simple closed from expression for the computation of the availability of a route, which can then be selected as the best route to serve the purposes of a specific application. Microsoft Visual C+ + was used for the purposes of running the simulation.